MORPHOLOGICAL CHARACTERISTICS OF BOSNIAN FIRST LEAGUE FEMALE BASKETBALL PLAYERS - Bašinac Ismet; Branimir Mikić; Haris Pojskić (Sport Scientific And Practical Aspects, 2025)
The aim of the research was estimation of anthropometric characteristics of female basketball players from six Bosnian first league teams and also identification of possible differences between the players that play at different positions in the teams. Forty three, actually health, players participated in this research. They were between nineteen and twenty four years old. For all eleven anthropometric characteristics, descriptive parameters have been calculated. For the identification of possible differences between the players that play at different positions in the teams multiple analysis of variance have been used. The obtained results show that there are not important differences between the players from different teams, but there are statistical significant differences between players that play at different team positions. They are expressed with all variables except one; lower leg length. Centers (big players) are dominantly with longer and wider skeleton dimensionality, as well as body mass. Values of these variables are bigger from players’ position one to position five. Further researches should include more anthropometric variables especially those for body voluminosity and body fat estimation that will help coaches to indirectly evaluate fitness level of tested players.